Measuring and calibrating non-common path aberrations in adaptive optics assisted image-slicer based spectrographs - Menduiña Fernández, A (2021)
HARMONI is the first-light, visible and near-IR integral field spectrograph for ESO’s Extremely Large Telescope (ELT), which promises to revolutionise observational astrophysics with its high spatial resolution, offering quasi-diffraction-limited performance from a ground-based observatory. The performance of Adaptive Optics assisted instruments such as HARMONI is hindered by the presence of differential aberrations between the AO wavefront sensing and science optical paths, known as NonCommon Path Aberrations (NCPA). These aberrations, which primarily affect the spatial point spread function (PSF) in HARMONI, cannot be sensed directly due to the absence of phase information in focal plane intensity measurements, so special techniques are needed to calibrate and pre-compensate them.